Lengthening Temporalis Myoplasty: Objective Outcomes and Site‐Specific Quality‐of‐Life Assessment. (4th July 2017) - Panciera, Davide Thomas; Sampieri, Claudio; Deganello, Alberto; Danesi, Giovanni
Abstract : Objective: Evaluate outcomes of the lengthening temporalis myoplasty in facial reanimations. Study Design: Case series with planned data collection. Setting: Ospedali Riuniti, Bergamo, and AOUC Careggi, Florence, Italy. Subjects and Methods: From 2011 to 2016, 11 patients underwent lengthening temporalis myoplasty; demographic data were collected for each. Pre‐ and postoperative photographs and videos were recorded and used to measure the smile angle and the excursion of the oral commissure, according to the SMILE system (Scaled Measurements of Improvement in Lip Excursion). All patients were tested with the Facial Disability Index, and they also completed a questionnaire about the adherence to physiotherapy indications. Results: All patients demonstrated a significant improvement in functional parameters and in quality of life. On the reanimated side, the mean z‐line and a‐value, measured when smiling, significantly improved in all patients: from 22.6 mm (95% CI, 20.23‐25.05) before surgery to 30.9 mm (95% CI, 27.82‐33.99) after surgery ( P <. 001) and from 100.5° (95% CI, 93.96°‐107.13°) to 111.6° (95% CI, 105.63°‐117.64°; P <. 001), respectively. The mean postoperative dynamic gain, passing from rest to a full smile at the reanimated side, was 3.1 mm (95% CI, 1.30‐4.88) for the z‐line and 3.3° (95% CI, 1.26°‐5.29°) for the a‐value. The Facial Disability Index score increased from a preoperative mean of 33.4 points (95% CI, 28.25‐38.66) to 49.9 points (95% CI, 47.21‐52.60) postoperatively ( P <. 001). Conclusions: The lengthening temporalis myoplasty can be successfully used for smile reanimation, with satisfying functional and quality‐of‐life outcomes.